Improving Fucoxanthin Production in Mixotrophic Culture of Marine Diatom Phaeodactylum tricornutum by LED Light Shift and Nitrogen Supplementation - Yang, Runqing; Wei, Dong (Frontiers in Bioengineering and Biotechnology, 2020)
Fucoxanthin, a kind of primary carotenoids in brown seaweeds and diatoms, has attractive efficacy in human’s healthcare including loss weight, the prevention of diabetes and Alzheimer’s disease. Marine diatom Phaeodactylum tricornutum is now realized as a promising producer for commercial fucoxanthin production due to its higher content of fucoxanthin than brown seaweeds with easily artificial cultivation and fucoxanthin extraction. In the present study, to improve fucoxanthin production in P. tricornutum, the mixotrophic cultures were applied to optimize initial cell density, light intensity, light regime and nitrogen supplementation. The results showed that the higher initial cell density (1×107 cells mL-1) and lower light intensity (20 μmol m-2 s-1) were favorable for biomass production and fucoxanthin accumulation. The maximal fucoxanthin content (16.28 mg g-1 dry weight) could be achieved under blue light, but the highest biomass concentration (5.53 g L-1) could be attained under red: blue light (R: B, 6:1) in the batch culture. A novel two-phase culture approach was developed to increase the biomass concentration to the highest value (6.52 g L-1) with the maximal productivity of fucoxanthin (8.22 mg L-1 d-1) through light shift from R:B ratio (6:1) in phase 1 to R:B ratio (5:1) by enhancing blue light and tryptone addition in phase 2. The content and intracellular amount of fucoxanthin were also increased 8% and 12% in phase 2 compared to phase 1. The expression levels analysis revealed that genes encoding phytoene synthase (PSY), zeaxanthin epoxidase (ZEP) and fucoxanthin-chlorophyll-protein b (FCPb) were upregulated significantly, with downregulation of the gene encoding violaxanthin de-epoxidase (VDE), leading to the improvement of fucoxanthin in phase 2. The present study demonstrated the two-phase culture strategy could promote fucoxanthin productivity through enhancing biomass production and increasing fucoxanthin content, indicating that strengthening blue light coupled with adding tryptone were effective to facilitate fucoxanthin production by mixotrophic cultivation of marine diatom P. tricornutum.